Kewajiban Negara terhadap Implementasi Perjanjian HAM Internasional dalam Perspektif Hukum Internasional Publik - Muhammad Fauzi; Shelilazoish Shelilazoish; Yosua Simamora; Mayzara Sari Fitria (CV. KAMPUS AKADEMIK PUBLISING, 2026)
International human rights treaties bind states to protect fundamental human rights. In the context of public international law, state obligations extend beyond ratification; they also encompass direct implementation at the national level through enforcement mechanisms, policy harmonization, and enforcement mechanisms. By reviewing public international law principles such as pacta sunt servanda and good faith, this article aims to examine how and where states should implement international human rights treaties.